Dependence of the paraffin content in paraffinic oils on the depth of occurrence in the non-Arctic (a) and Arctic territories of Russia (b) ... - Yashchenko, Irina; Polishchuk, Yurii (Cifra LLC, 2024)
Cifra. Химия, Выпуск 3 (3) 2024 ...